SOSIAL KAPITAL MASYARAKAT DALAM OPERASIONAL DAN PEMELIHARAAN DAERAH IRIGASI KRUENG ACEH - Sukandar, Sukandar; Masimin, Masimin; Fatimah, Eldina (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2018)
Abstract: Krueng Aceh Irrigation Area in Aceh Besar District is expected to be able to improve the community economic growth and to support food self-sufficient in Aceh Besar District. To meet the expectation, It must be supported by the good and organized irrigation systems. So that Krueng Aceh Irrigation Network must have irrigation network system management which include of operational and maintenance activities (OP). This research aims to detect the existing condition of Krueng Aceh Irrigation Network in Blang Bintang Subsection, find out community role level in Water User Farmer Group (P3A) relating to existing irrigation network operational and maintenance activities, then formulating the system strategy operational and maintenance activities of Krueng Aceh Irrigation System. The method used to analyze the data in this research is descriptive and analysis SWOT. Based on the observation result, the irrigation network existing condition finding some damages in the canals, there are sediment and waste found in the canal, the livestock can be found both tied and not surrounding the irrigation network. According to the result of questionnaire distribution to the respondents, it can be concluded that the community and the water user farmer group (P3A) are not active in irrigation network operational and maintenance activities. The SWOT analysis results is obtained the strategies such as (1) improving the water management system operationally to do the efficiency of irrigation water utilization; (2) Improving the Human Resources quality by giving the socialization to the farmer community in improving the farmer production and implementation of irrigation network operation and maintenance activities; (3) Reactive the water user farmer group (P3A) in managing and maintaining the irrigation network; (4) Improving the role and responsibility of the P3A committee as well as community in maintaining the irrigation network; and (5) Improving the community awareness by growing the communal activity culture in maintaining the irrigation network both routine and periodic.Abstrak: Jaringan Irigasi Krueng Aceh di Aceh Besar diharapkan mampu meningkatkan pertumbuhan ekonomi masyarakat serta menunjang swasembada pangan di Kabupaten Aceh Besar. Untuk memenuhi harapan tersebut harus didukung oleh adanya sistem irigasi yang baik dan terorganisir. Untuk itu Jaringan Irigasi Krueng Aceh harus memiliki sistem pengelolaan jaringan irigasi meliputi kegiatan operasional dan pemeliharaan (OP). Tujuan dari penelitian ini adalah mengetahui kondisi eksisting Jaringan Irigasi Krueng Aceh di Wilayah Ranting Blang Bintang, mengetahui tingkat peran masyarakat Perkumpulan Petani Pemakai Air (P3A) berkenaan dengan operasional dan pemeliharaan jaringan irigasi yang ada. Dan merumuskan strategi sistem operasional dan pemeliharaan saluran irigasi Krueng Aceh. Metode pengumpulan data yaitu menggunakan data sekunder dan data primer. Data diolah secara statistik diskriptif dan analisis SWOT. Dari hasil observasi, kondisi eksisting terdapat kerusakan pada sebahagian saluran, banyak terdapat sedimen dan tumpukan sampah dan adanya hewan peliharaan yang diikat maupun dilepas di sekitar jaringan irigasi. Hasil penyebaran kuesioner kepada responden, dapat disimpulkan bahwa masyarakat dan perkumpulan petani pemakai air (P3A) tidak aktif dan melaksanakan operasional dan pemeliharaan jaringan irigasi. Hasil analisis SWOT diperoleh strategi-strategi yaitu (1) meningkatkan sistem pengaturan air irigasi secara operasional untuk melakukan efesiesi dalam penggunaan air irigasi; (2) meningkatkan kualitas SDM dengan memberikan sosialisasi, kepada masyarakat petani dalam meningkatkan produksi tani serta pelaksanaan operasional dan pemeliharaan jaringan irigasi; (3) mengaktifkan kembali perkumpulan petani pemakai air (P3A) dalam mengelola dan memelihara jaringan irigasi; (4) meningkatkan peran dan tanggung jawab pengurus (P3A) serta masyarakat dalam memeliharan jaringan irigasi; dan (5) meningkatkan kesadaran masyarakat dengan menumbuhkan budaya gotong royong dalam memeliharan jaringan irigasi baik secara rutin maupun berkala